2002
DOI: 10.1021/np020239o
|View full text |Cite
|
Sign up to set email alerts
|

New Onoceranoid Triterpene Constituents from Lansium domesticum

Abstract: Three new natural onoceranoid triterpenes, lansionic acid (1), 3beta-hydroxyonocera-8(26),14-dien-21-one (2), and 21alpha-hydroxyonocera-8(26),14-dien-3-one (3), were isolated from the fruit peel of Lansium domesticum together with two known triterpenoids (4 and 5), and their structures were elucidated from spectral data. These triterpenoids exhibited mild toxicity against brine shrimp (Artemia salina).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 8 publications
1
44
0
3
Order By: Relevance
“…Hal yang sama diperoleh pada profil KLT dari ekstrak etanol kulit langsat (KLE) dan ekstrak etil asetat kulit langsat (KLEA) masing-masing adanya spot yang menunjukkan golongan senyawa flavonoid dan steroid/terpenoid. Hal ini sesuai dengan beberapa literatur yang menjelaskan bahwa L.domesticum memiliki kandungan senyawa flavonoid dan steroid/terpenoid (Klungsupya et al, 2015;Nishizawa et al, 1982Nishizawa et al, , 1989Tanaka et al, 2002).…”
Section: Hasil Dan Pembahasanunclassified
“…Hal yang sama diperoleh pada profil KLT dari ekstrak etanol kulit langsat (KLE) dan ekstrak etil asetat kulit langsat (KLEA) masing-masing adanya spot yang menunjukkan golongan senyawa flavonoid dan steroid/terpenoid. Hal ini sesuai dengan beberapa literatur yang menjelaskan bahwa L.domesticum memiliki kandungan senyawa flavonoid dan steroid/terpenoid (Klungsupya et al, 2015;Nishizawa et al, 1982Nishizawa et al, , 1989Tanaka et al, 2002).…”
Section: Hasil Dan Pembahasanunclassified
“…Most compounds containing in the seed of Longkong are tetranorterpenoids, including domesticulide A-E, with 11 known triterpenoids. Six classes of limonoids have been isolated from the seed extracts of L. domesticum, including andirobin derivates, methyl angolensates, mexicanolides, azadiradiones, onoceranoids, and dukunolides (Tanaka et al, 2002). Sassa et al have demonstrated the inhibitory effect of the dienone-phenolic triterpene on lipid peroxidation in rat liver mitochondrial membranes induced by ADP and Fe 2þ (Sassa et al, 1990).…”
Section: Lipid Peroxidation Inhibition Activitymentioning
confidence: 99%
“…(Apocynaceae) is a small tree widely distributed over the northern Malayan peninsula and other south Asian areas, and its milky lotion has been used as a folk medicine. 1) During our search for bioactive natural products from tropical plants, 2) we investigated the chemical constituents of leaves of W. javanica collected in Thailand.…”
mentioning
confidence: 99%
“…Here we describe the isolation and structure elucidation of two new pregnane alkaloids, wrightiamines A (1) and B (2), and preparation of compound 2 to establish the C-20 configuration. 1 exhibited cytotoxic activity against vincristine-(VCR)-resistant murine leukemia P388 cells, while the cytotoxicity of 2 was weak.…”
mentioning
confidence: 99%
See 1 more Smart Citation